Groups VI. (London : Waddington Galleries, 1983)
Arp, Jean ; Auerbach, Frank ; Avery, Milton ; Baselitz, Georg ; Blake, Peter ; Bonnard, Pierre ; Calder, Alexander ; Caulfield, Patrick ; Cézanne, Paul ; De Stael, Nicolas ; Dubuffet, Jean ; Dufy, Raoul ; etc.
Groups VI, Waddington Galleries, London, 2 February - 26 February 1983
boek